(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Naipaul’s work has been portrayed as an examination of the clash among belief and unbelief, the unraveling of the British Empire, and the migration of people. Controversial, both regarding his impression of postcolonial nations and of postcolonial literary criticism, Naipaul, who won the Nobel Prize for Literature in 2001, at an earlier point declared the novel dead and postcolonial nations half-baked. Notwithstanding his provocative professions and his readers’ criticisms (the most stringent and broad evaluations), Naipaul is too important to even consider being marginalized. While major contemporaries have ceased to be gainful (Walcott, Ondaatje, Soyinka) Naipaul’s voice keeps on being heard, his tones new, his viewpoint sufficiently adaptable to apprehend new phenomena in culture and politics, and his evaluate adequately aggravating to justify critical attention. In spite of accusations of being a postcolonial lackey, a reactionary, a racist, and a sexist, he has endured, and not just because of his elegant exposition. In this article we will learn about the advancement of job of the marginalized groups in the novels Half a Life and Magic Seeds of V S Naipaul.